User-centred design of ehealth solutions for home dialysis: focus on patient experience and clinicians’ needs - Hölsä, Sini; Valkonen, Paula; Viitanen, Johanna; Rauta, Virpi (Finnish Journal of eHealth and eWelfare, 2022)
New eHealth solution for home dialysis patients and clinicians aims to support and make the care process more fluent. Taking the end-users into account and involving them in the development process is important for wide adaption and truly useful outcome. In this article, we present research, which aims to identify the needs and experiences of home dialysis patients and their clinicians with a new eHealth solution, which includes different instruments and sensors along with an application. This research is a part of a larger research project called ‘eHealth in Home Dialysis’. Research data was collected from two remote workshops with five patients and four clinicians that were held at the end of 2021. Previous data (interviews and usability evaluations) from the same research project were utilized in the planning of these workshops. The workshop data were analyzed with qualitative methods. Home dialysis patients had some experience with the new eHealth solution, and they saw potential in the unity with different instruments, sensors, and an application. Following up the results of measurements and data-based decision-making regarding own care were seen as the most important features of the eHealth solution. However, continuous measuring and form filling was seen laborious at times. In addition, the usability of the smartwatch was unsatisfactory. Clinicians, on the other hand, had not used the new eHealth solution, but they were aware of it. From the perspective of clinicians, the new eHealth solution should fit their working environment and processes with other IT solutions. Clinicians saw potential in the eHealth solution as it could ease defining the general condition of a patient and following up the patient’s status together with the patient. However, resources and guidance regarding the implementation is needed. The new eHealth solution has potential but planning and designing regarding the principles of the use of eHealth solutions between patients and clinicians is needed before wider implementation. Further development of solutions should focus on usability and integration with current IT systems so that the use of eHealth solutions can be a fluent and easy part of home dialysis care both from patients’ and clinicians’ perspective. eHealth solutions could encourage more patients to choose home care in the future, which compared to hospitalization requires less resources and can better support individualized care.